A new species of Cylindrophis Wagler, 1828 (Reptilia: Squamata: Cylindrophiidae) from Boano Island, northern Maluku Province, Indonesia - Kieckbusch, Max; Mader, Felix; Kaiser, Hinrich; Mecke, Sven (Zootaxa, 2018)
We describe a new species of snake of the genus Cylindrophis Wagler, 1828 from Boano Island, northern Maluku         Province, Indonesia. Cylindrophis osheai sp. nov. differs from all congeners by a combination of the following eidonomic characters: (1) 19 dorsal scale rows at midbody; (2) 224−226 ventral scales; (3) 8−9 subcaudal scales; (4) 25−28 dark ventral blotches, aligned to form a broad, wavy stripe along most of the body; (5) a dark ventral pattern that is completely separated from the dark dorsal coloration; (6) an almost completely dark ventral surface on the tail; (7) a dark bar running from the eye through the 3rd and 4th supralabials to the mouth; and (8) a dark, double-diamond-shaped ventral blotch in the area immediately posterior to the genials. Eidonomic species separation from other Cylindrophis species is supported by differences in cranial osteology, as elucidated by micro-computed tomography images. Diagnostic features of the cranium include (1) well-developed postorbitofrontals that project laterally beyond the maxilla in dorsal view, creating a characteristic, horn-like appearance; (2) a broad parietal with a bulbous middle section; (3) 10–12 maxillary teeth; (4) nine        palatine teeth; (5) 7–9 teeth on the pterygoid; and (6) 11–13 teeth on the dentary. We also provide notes on the taxonomic history of Cylindrophis melanotus Wagler, 1828 and an identification key to the Moluccan species of the genus.